A Virtual Reconstruction Methodology for Archaeological Heritage in East Asia – Practical Experience from the Re-relic Program in China - Yan He (Virtual Archaeology Review, 2013)
There is as much abundance of archaeological heritage in East Asia as there is diversity in the methodology for its reconstruction and representation. The Re-relic program in China recognizes the uniqueness of archaeological heritage in East Asia and has developed a tailored virtual reconstruction methodology that is both scientifically robust and popular for public interpretation. The theoretical consideration and field experience over the years shall contribute to the global understanding of the value and technique in virtual reconstruction, while testifying to the very principles of Seville Charter.